Students’ Motivation in Learning English - Yulfi Yulfi; Ahwalusah Aalayina (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study aims to determine students' motivation in learning English and its effect on their English learning achievement. The research method used is survey research with a quantitative approach. Data were collected using questionnaires, interviews, and documentation. The questionnaire was adapted from the Attitude Motivation Test Battery (AMTB) designed by Gardner. The results showed that 52% of students took an active role in learning English. Students are relative "highly" motivated to learn English to have a good chance in their educational goals. In conclusion, instrumental motivation is a significant factor among students of SMAN 5 Lubuklinggau in learning English. Based on data documents about students' English scores, students' motivation to learn English affects their English learning achievement. Keywords: English, Learning, Motivation